2020
DOI: 10.1557/jmr.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories, diffusion, and interactions of single ceria particles on a glass surface observed by evanescent wave microscopy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…Two entirely different particle motions of single ceria particles in 2D (x-y) plane were observed at pH 7 [12]. As explained above, the motion of particle 1 was similar to the confined motion that was observed at pH 3 and 5.…”
Section: D Trajectory Analysis Of a Single Ceria Particle With Confisupporting
confidence: 61%
See 3 more Smart Citations
“…Two entirely different particle motions of single ceria particles in 2D (x-y) plane were observed at pH 7 [12]. As explained above, the motion of particle 1 was similar to the confined motion that was observed at pH 3 and 5.…”
Section: D Trajectory Analysis Of a Single Ceria Particle With Confisupporting
confidence: 61%
“…In Fig. 3, the time evolution of these positions can be visualized from the color scheme that changes gradually from red initially (t = 0) to blue at t = 20 s. The movements of single ceria particles at pH 3 and 5 are confined to a relatively small area of 15 × 15 nm 2 and 30 × 30 nm 2 , respectively, due to strong attractive electrostatic and van der Waals forces (zeta-potentials of ceria particle at pH 3 and 5 are 70 and 50 mV, respectively, and that of SiO 2 film is −20.0 mV) [12]. The isoelectric point (pH IEP ) of the glass (SiO 2 ) film is 2.0, resulting in a negatively charged glass surface in the pH range we are interested in.…”
Section: D Trajectory Analysis Of a Single Ceria Particle With Confimentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al reported that the change (ΔpH) in the pH of silica and ceria slurries as the temperature increased from 20 to 90°C was ∼1.0 and ∼1.3, respectively [116,119]. It is well known that a change in pH of slurry has a significant influence on the particle-wafer interactions [123,124]. Also, the solubility of oxygen in water decreases with increasing temperature [125].…”
Section: The Effect Of Temperature Changes On the Chemical And Mechanical Reactions During Polishingmentioning
confidence: 99%